Anticarcinogenic Effects of Dried Citrus Peel in Colon Carcinogenesis Due to Inhibition of Oxidative Stress. (18th August 2017) - Onuma, Wakana; Asai, Daichi; Tomono, Susumu; Miyamoto, Shingo; Fujii, Gen; Hamoya, Takahiro; Nagano, Aya; Takahashi, Satoru; Masumori, Shoji; Miyoshi, Noriyuki; Wakabayashi, Keiji; Mutoh, Michihiro
ABSTRACT: Colorectal cancer is one of the leading causes of death worldwide. Reactive oxygen species produce oxidative stress and contribute to colorectal carcinogenesis. Because dietary citrus has been shown to reduce oxidative stress, we investigated the effects of citrus peel extract at dilutions of 1/200–1/500 on the activity of oxidative-stress-related transcription factors, including AP-1, NF-κB, NRF2, p53, and STAT3, in human colon cancer cell line HCT116 cells using a luciferase reporter gene assay. NRF2 transcriptional activities were 1.8- to 2.0-fold higher than the untreated control value. In addition, NF-κB, p53, and STAT3 transcriptional activities were 12–26% lower than the untreated control value. Administration of dried citrus peel in the diet of F344 rats at a dose of 1, 000 ppm prevented the formation of azoxymethane-induced precancerous aberrant crypt foci (ACF) in the colon. The total number of ACF in rats fed with dried citrus peel was reduced to 75% of the control value. Moreover, the levels of oxidative-stress-related markers, reactive carbonyl species, in the serum of F344 rats were significantly reduced following the administration of dried citrus peel. These data suggest that citrus peel possesses an ability to suppress cellular oxidative stress through induction of NRF2, thereby preventing azoxymethane-induced colon carcinogenesis.